1976
DOI: 10.1159/000280026
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Sensitivity of α-Receptors in the Urethra Musculature

Abstract: Estrogene has a tonicising effect upon urethra musculature. There is also the same demonstrable influence of α-receptor stimulating drugs upon the urethra pressure profile. After preliminary treatment with estrogene, there is a considerably stronger tonicising effect of α-stimulating drugs than without such a treatment. So the combination of estrogene and α-stimulating drugs seems a useful addition to the conservative treatment of stress incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 1 publication
0
37
0
3
Order By: Relevance
“…We could not confirm the finding of Caine and Raz (2) who demonstrated an increased urethral closure pressure after treatment with estrogens. Estrogens may, however, be of therapeutical value in the conservative treatment of stress incontinence especially if supplemented with a-sympathomimetic drugs as reported by Schreiter et al (10).…”
Section: Discussionmentioning
confidence: 95%
“…We could not confirm the finding of Caine and Raz (2) who demonstrated an increased urethral closure pressure after treatment with estrogens. Estrogens may, however, be of therapeutical value in the conservative treatment of stress incontinence especially if supplemented with a-sympathomimetic drugs as reported by Schreiter et al (10).…”
Section: Discussionmentioning
confidence: 95%
“…All ofour patients were treated with long-term oral estrogen, and the effect of this therapy on the muscle bath results cannot be evaluated by the present data. Hormonal manipulation has been reported to alter the in vivo and in vitro response of other tissues to adrenergic stimulation (30)(31)(32)(33). The responses obtained in the estrogentreated humans are qualitatively identical, however, to those seen in nonhormonally treated monkeys (19).…”
Section: Discussionmentioning
confidence: 99%
“…If for some reason medical treatment is indicated, the use of an alpha-receptor stimulator is currently accepted as the drug of choice. The drug effect on the urethral pressure is well documented [2][3][4][5][6] but the clinical re sponse reported so far seems to be moderate [7], The uro dynamic parameters used for the evaluation have in pre vious reports mainly been the maximal urethral closure pressure (MUCP) at rest and the functional urethral length. However, genuine stress incontinence is not char acterized by disturbances of these parameters alone, but by insufficient pressure transmission to the urethra at the moment of sudden increase in the abdominal pressure [8], Changes in the pressure transmission ratio (PTR) are therefore the most important urodynamic parameter for diagnosis as well as for the evaluation of treatment [9], In some previous reports phenylpropanolamine (PPA) has been used as an alpha receptor-stimulating drug [2,7], but serum concentration studies about the clinical and urodynamic effect of the drug have not been reported.…”
Section: Introductionmentioning
confidence: 99%